وەبەرهينان له بازاری دراو و بورسەدا - حسن, نەوزاد محمد (Sulaimani Journal for Humanities, 2001)
This research is consent of investment in financial markets wish is men the process of buying and selling financial paupers or changing the property rights for production powers. Actually we can do a comparative between the real investments which is means additional to production to the capital accumulation. In the progress countries this markets growth before many years, but in the poor countries this markets appiras before twenty years ago. We try to put the light on the natural and types of these markets. We also appointed to same factors wish is rool in this markets wish same of them illegally which make this markets to be under shaiking and playing which is effect to destroy the financial markets, as happened in financial national collaph in 1929 - 1933 and in Mali Zia, Indonesia and Korea in 1997.